A 1D eye tissue model to mimic retinal blood perfusion during retinal imaging photoplethysmography (iPPG) assessment: a diffusion approximation - finite element method (FEM) approach / Harnani Hassan ... [et al.] - Hassan, Harnani; Herman, Sukreen Hana; Mohamad, Zulfakri; Sijung, Hu; Vincent M., Dwyer (2021)
This paper presents a one-dimension (1D) eye tissue model to mimic retinal blood perfusion during retinal imaging photoplethysmography (iPPG) assessment in previous work. An uneven light source illumination and noise during the assessment can affect the extraction of backscattering light, hence alter the actual blood perfusion measurement. In this work, a simplified eye model that consists of four layers: retina, retina epithelium (RPE), choroid, and sclera was employed to perform numerical analysis using diffusion approximation - Finite Element Method (FEM) approach. The analysis has utilized optical properties of healthy eye tissue and the simulation was performed in the MATLAB 2019a environment. The outcomes of alternate current (AC) component and fluence rate show that the proposed approach can be utilized to mimic retinal blood perfusion in different tissue depths and predict the amplitude of the generated pulsatile waveform before starting an assessment. The simulation consumed less computation time to analyze and the generated pulsatile was uncontaminated with noise.